DIGITAL PROGRESS TRENDS IN NATIONAL PHYSICAL EDUCATION AND SPORTS SECTOR - Petrov, P.K. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to analyze the digital transformation experience in the physical education and sport sector on the whole and the physical education and sport specialist education system in particular. Methods and structure of the study. We used in the study the following methods: analysis of the relevant theoretical and practical study reports; and summary of our own practical experience in the physical-education-and-sport-specific digital information technologies schooling, design and application. Results and conclusion. Our analysis of the relevant theoretical and practical study reports and practical digital transformation implementation experiences in the national physical education and sport sector showed the physical education and sport specialist education, retraining and advanced training service being one of the most promising digital transformation progress trends. In this context, a special priority in the physical education-and-sport-specific digital transformation development projects will be given to the advanced training of the academic faculties to help them establish and use modern e-learning resources, develop knowledge and skills in a variety of modern online and mixed education service formats, and keep abreast with the modern physical education-and-sports-education-specific digital transformation progress trends to ensure high quality of their students’ professional service in future.